THE INFLUENCE OF CANVA MEDIA ON THE LEARNING OUTCOMES OF CLASS VI STUDENTS IN INTRODUCTION TO THE SOLAR SYSTEM AT SDN 61 BANDA ACEH - Rusmaini; Siti Mayang Sari; Akmaluddin (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
This research is entitled The Influence of Canva Media on Learning Outcomesof Class VI Students on Introduction to the Solar System at SDN 61 BandaAceh. Using a qualitative descriptive approach with data collection techniquesused are observation, interviews and literature studies. This discussion concernsthe influence of the Canva application as a learning medium for learning aboutthe solar system. Learning media is needed by teachers in supporting andsupporting teaching in education. Media is a tool used by teachers in teaching,apart from using books or lecture methods, teachers are also expected to havedifferent learning media and adapt the material and conditions to theirrespective students. Technological developments are increasingly rapid andadvanced, everyone is expected to understand technology as a support for allexisting activities, as well as in the realm of education. Teachers and studentscan take advantage of technology-based learning media, one of which is theCanva application. Canva is an online-based application that provides attractivedesigns in the form oftemplate, features, and the categories given in it. Withvarious and attractive designs, it makes the learning process not boring. Byusing the Canva application, teachers can teach students knowledge, creativity,and skills so that this media can also be used in various areas of life.This research is entitled The Influence of Canva Media on Learning Outcomesof Class VI Students on Introduction to the Solar System at SDN 61 BandaAceh. Using a qualitative descriptive approach with data collection techniquesused are observation, interviews and literature studies. This discussion concernsthe influence of the Canva application as a learning medium for learning aboutthe solar system. Learning media is needed by teachers in supporting andsupporting teaching in education. Media is a tool used by teachers in teaching,apart from using books or lecture methods, teachers are also expected to havedifferent learning media and adapt the material and conditions to theirrespective students. Technological developments are increasingly rapid andadvanced, everyone is expected to understand technology as a support for allexisting activities, as well as in the realm of education. Teachers and studentscan take advantage of technology-based learning media, one of which is theCanva application. Canva is an online-based application that provides attractivedesigns in the form oftemplate, features, and the categories given in it. Withvarious and attractive designs, it makes the learning process not boring. Byusing the Canva application, teachers can teach students knowledge, creativity,and skills so that this media can also be used in various areas of life.